The Transition from Song to Poetry in Latvian Literature in the Second Half of the 19th Century - Māra Grudule (Interlitteraria)
The Latvian nation is a singing nation. The Singing Revolution and similar song- and singing-related references are traditionally associated with the image of Latvians. The origins of written Latvian are also related to song: the oldest known Christian song in Latvian, dating from 1530, is also one of the oldest examples of Latvian-language text.